The Identity Negotiation of the New Muslim Converts in Iran (with Emphasis on the Role of Islam) - Saeid Reza Ameli; Gholamreza Solgi; Maryam Razani; Mansore Hejazi; Zahra Karami; Rozhan Eskandar; Faeze Mostofi (Taḥqīqāt-i Farhangī-i Īrān, 2015)
Typically, people deal with their environment and talk about their identity, and shape their identity with the results of such negotiations. In situations where the person experiences changes like migration or converting to a new religion in his life, the negotiations will be intensified in order to adapt to  the new findings, and leads him/her to choose strategies to adapt to these changes and to reach a new identity. Now the question is: what strategies does the Newly Muslim choose in Iran about the factors of identity, such as name, dress, entertainment, relationships (with friends and relatives), Sharia (Islamic Laws) and prayers and financial issues in order to achieve a new identity? What aspects of the Identity of the New Muslim Converts are distinct from their identity before Islam? What aspects of their former identity have continued and what are their specific features?   The study has been conducted in two stages by interviewing many converts, and with the categorization of the interviews, nine strategies have been extracted about the negotiation of New Muslim Converts’ identity with the Iranian society.